(untitled) (Community Based Medical Journal, 2026)
At the base of skull in occipital bone, there is a large oval opening called the foramen magnum through which the cranial cavity communites with the vertebral canal. The squamous part of the occipital bone makes up the posterior portion of foramen magnum, while the basilar part makes up the anterior portion. A cross-sectional, analytical study was conducted in the Department of Anatomy, Dhaka Medical College, Dhaka, Bangladesh, from January to December of 2022, to observe sexual dimorphism of foramen magnum in a Bangladeshi population. One hundred and twenty dry adult human occipital bone was collected for the measurement of the foramen magnum. We adopted convenient purposive sampling technique. However, occipital bone having fractured or if a part of occipital bone was missing or incomplete occipital bone was excluded to construct standard measurement. Measurements were done by using digital Vernier slide calipers. The length of the foramen magnum in male was greater than that of female; the difference was statistically significant (34.47±0.84mm vs. 32.83±0.96mm; p<0.001). The width of the foramen magnum was greater in male than that of female; the difference was statistically significant (29.01±1.23mm vs. 27.43±0.82mm; p<0.001). CBMJ 2026 January: vol. 15 no. 01 P:74-77